The girlfriend - Stine, R. L. (New York : Scholastic, 1991)
Scotty meets a new girl while his girlfriend is out of town. His one wild night becomes a nightmare when she decides she loves him to death!
Young Adult
Keywords: Horror tales -- Juvenile fiction; Horror tales -- Fiction; Horror fiction; Horror fiction